2017
DOI: 10.1002/jcp.25861
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin induces death of prostate cancer cells by inducing ROS and ER stress

Abstract: Chrysin is a natural flavone found in numerous plant extracts, honey, and propolis that has multiple biological activities including anti-cancer effects. Understanding of biological mechanisms mediated in response to chrysin in cancerous cells may provide novel insight into chemotherapeutic approaches with reduced side effects in cancers. In the present study, we investigated functional roles of chrysin in progression of prostate cancer cells using DU145 and PC-3 cell lines. The results showed that chrysin ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(64 citation statements)
references
References 42 publications
4
60
0
Order By: Relevance
“…Previous studies indicate that chrysin reduces cell viability by the activation of cytochrome c and caspase‐3 and ‐9 in human uveal melanoma cells (Xue et al, ). In addition, treatment with chrysin induces abundant ROS generation, leading to lipid peroxidation and alteration of mitochondrial membrane permeabilization in apoptosis of human prostate cancer cells (Ryu et al, ). In accordance with previous researches, chrysin exerted antiproliferative and apoptotic effects on human ovarian cancer cells by inducing ROS production and depolarizing MMP in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that chrysin reduces cell viability by the activation of cytochrome c and caspase‐3 and ‐9 in human uveal melanoma cells (Xue et al, ). In addition, treatment with chrysin induces abundant ROS generation, leading to lipid peroxidation and alteration of mitochondrial membrane permeabilization in apoptosis of human prostate cancer cells (Ryu et al, ). In accordance with previous researches, chrysin exerted antiproliferative and apoptotic effects on human ovarian cancer cells by inducing ROS production and depolarizing MMP in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Chrysin inhibits the growth of lung cancer cells, leading to apoptosis by the activation of caspase-3 and caspase-9, and an increase of the proapoptotic protein, B-cell lymphoma-associated X protein (Bax) (Samarghandian, Nezhad, & Mohammadi, 2014). It stimulates apoptotic events in prostate cancer cells by the accumulation of DNA fragmentation, an increase in the population of cells in the sub-G 1 phase of the cell cycle, and activation of ERK1/2 and p38 proteins (Ryu, Lim, Bazer, & Song, 2017). In addition, chrysin induces cell cycle arrest by reducing cyclin-dependent kinase 2 and 4, and activating p38, leading to the accumulation of p21(Waf1/ Cip1) protein in glioma in vitro (Weng, Ho, & Lin, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In detail, the treatment of HCT-116 cell line with 5-hydroxy-7-methoxyflavone led to ROS generation and Ca 2+ release, resulting in ER stress induction. Simultaneously, 5-hydroxy-7-methoxyflavone causes alterations in mitochondrial membrane potential (MMP) and a reduction of the Bcl-2/Bax ratio, leading to activation of caspase-3 and apoptosis progression [32].…”
Section: Flavonoid Derivatives and Phenolic Compoundsmentioning
confidence: 99%
“…9,10 Recent reports have shown that ER stress is related to apoptosis and the occurrence and progression of tumors. 11,12 Therefore, we speculate that SIL1, as a key regulator of ER function, might have a specific role in tumor development.…”
Section: Introductionmentioning
confidence: 98%